The London bombings : an independent inquiry - Ahmed, Nafeez Mosaddeq (London : Duckworth, 2006)
On July 7th 2005 London experienced its most serious terrorist attack since the V-2 raids of WW2. This investigation reveals for the first time the full extent of the links between UK intelligence and terrorists based in Britain.
Introduction: July 2005 -- A month under siege (part I) -- A month under siege (part II) -- 7/7: paralysis of the national security system -- Conclusions and recommendations.
Some pages marked "Section removed for legal reasons."
Includes bibliographical references.
Keywords: 2005; London Terrorist Bombings, London, England, 2005.; Terrorism -- Government policy -- Great Britain; Islamic fundamentalism; Terrorism -- Government policy; England -- London; Great Britain